Arroz integral na dieta de frangos de corte - Souza, Maria Consuelo Silva de (2012)
A trial was conducted to evaluate the replacement of corn by whole rice in poultry diets. A total of 384 one day old Coob broilers were used. The chicks were randomly allotted to four treatments and eight replications of 12 birds each. The birds were reared in dark house during 42 days. A completely randomized design was used. Treatment means were compared by orthogonal contrasts and polynomial regression at 5%. The following treatments were tested: T1 100% corn as the main energy source; T2 33% whole rice in replacement of corn; T3 - 66% whole rice in replacement of corn; T4 100% whole rice as the main energy source in full replacement of corn. Body weight, weigh gain, feed consumption and feed per gain ratio were measured. Carcass traits included: thigh and drumstick, back, chest, wing and wing thigh. Birds fed diets containing 33% whole rice in substitution of corn (T2) and also 100% whole rice in substitution of corn (T4) showed a higher average body weight (P<0.01). No significant difference was observed for weigh gain, feed per gain ratio, thigh yield, thigh and drumstick yield, back yield, chest yield, and wing and wing thigh yield. In conclusion, corn can be replaced by whole rice in poultry diets with no negative effects on either performance or carcass traits.